Facilitating the Development of German Listening Competence at B1 Level for German Language Teachers in Makassar: Pendampingan Pengembangan Kompetensi Menyimak Bahasa Jerman Level B1 untuk Guru Bahasa Jerman di Makassar - Asnur, Muhammad Nur Ashar; Triswantini, Erna; Uryadi (Mattawang: Jurnal Pengabdian Masyarakat, 2024)
Teachers play a crucial role in the success of education and bear significant responsibilities towards both students and the state. Consequently, it is expected that teachers possess the competencies established by law, which include pedagogical, personal, professional, and social competencies. Competency enhancement can be achieved through training and various other activities, one of which is the Subject Teacher Consultation (MGMP). Within the MGMP for German language teachers, there is a pressing need to improve teachers' professional competencies in linguistic aspects. A B1-level German language training program has been designed to assist teachers with their listening skills by providing model questions and tips for international certification exams. The training outcomes indicate a significant improvement in participants' scores, moving from a satisfactory to a good category. Therefore, it is recommended that this training be continued, with the possibility of conducting it in person in the future. Abstrak Guru memainkan peran kunci dalam keberhasilan pendidikan dan memiliki tanggung jawab besar terhadap siswa dan negara. Oleh karena itu, guru diharapkan memiliki kompetensi yang ditetapkan oleh undang-undang, yaitu kompetensi pedagogik, kepribadian, profesional, dan sosial. Peningkatan kompetensi dapat dilakukan melalui pelatihan dan kegiatan lainnya, salah satunya melalui Musyawarah Guru Mata Pelajaran (MGMP). Dalam MGMP Bahasa Jerman, terdapat kebutuhan untuk meningkatkan kompetensi profesional guru dalam aspek kebahasaan. Pelatihan bahasa Jerman tingkat B1 dirancang untuk membantu guru dalam keterampilan menyimak, dengan menyediakan model soal dan tips untuk ujian sertifikat internasional. Hasil pelatihan menunjukkan peningkatan signifikan dalam skor peserta, dari kategori cukup menjadi baik. Oleh karena itu, pelatihan ini diusulkan untuk dilanjutkan, dengan kemungkinan pelaksanaan secara luring di masa mendatang.